«Modicæ fidei quare dubitasti?» Una lectura del pontificado de Calixto III (1455-†1458) a partir de las imágenes monetales. - AGUILERA, ALBERTO (Scripta, 2017)
This article studies the pontificate of Calixtus III (1455-†1458) from the propaganda function and communicational dimension of the images and inscriptions appearing on papal coinage. Attention is paid to points of continuity with the monetary issues of his predecessors on the throne of St. Peter, as well as novelties introduced in relation to the planned crusade against Islam.